2021
DOI: 10.2174/2210315510666200131114525
|View full text |Cite
|
Sign up to set email alerts
|

Barleria prionitis L.: An Illustrative Traditional, Phytochemical and Pharmacological Review

Abstract: : Barleria prionitis, a small perpetual, prickly shrub, belongs to the family Acanthaceae, normally called “porcupine flower” or “Vajradanti” with a lot of vernacular names. It is an indigenous herb of Southern Asia and some regions of Africa. The therapeutic use of leaf, flower, stem, seed, shoot, root and in certain cases complete herb of B. prionitis against numerous disorders including cough, fever, jaundice, asthma, severe pain, acne, cut wound are recognized by ayurvedic and other conventional medicinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Several species of Barleria are known for their medicinal or ornamental values [ 6 , 43 , 55 ]. There have been studies reviewing the traditional, phytochemical, and pharmacological properties of certain species of Barleria , such as B. lupulina and B. prionitis [ 56 , 57 , 58 ]. Ghosh et al, 2012 [ 59 ] have studied the vegetative and floral characters of B. cristata , B. lupulina , B. prionitis , and B. strigosa .…”
Section: Discussionmentioning
confidence: 99%
“…Several species of Barleria are known for their medicinal or ornamental values [ 6 , 43 , 55 ]. There have been studies reviewing the traditional, phytochemical, and pharmacological properties of certain species of Barleria , such as B. lupulina and B. prionitis [ 56 , 57 , 58 ]. Ghosh et al, 2012 [ 59 ] have studied the vegetative and floral characters of B. cristata , B. lupulina , B. prionitis , and B. strigosa .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should be conducted using different assays on clinical isolates and not only standard strains of the virus. Chen et al [ 87 ] also reported about the isolation of iridoid glycosides (6- O - trans - p -coumaroyl-8- O -acetylshanzhiside methyl ester and its cis isomer) from the methanolic extracts of B. prionitis , and these extracts were found to exhibit potent in vitro activity against the respiratory syncytial virus (EC 50 2.46 μg/mL, IC 50 42.2 μg/mL) [ 54 ].…”
Section: Biological Activities Of Extracts Fractions and Isolated Compounds From Barleriamentioning
confidence: 99%
“…Several species of Barleria are known for their medicinal or ornamental values [ 37 , 52 , 53 ]. There have been studies reviewing the traditional, phytochemical and pharmacological properties of specific species of Barleria (e.g., B. lupulina and B. prionitis ) [ 54 , 55 , 56 ], however none have comprehensively reported on species within Barleria using exisiting literature in a clear and concise manner. Therefore, this review is intended to elaborate on only the important and extensively studied species belonging to the genus Barleria , with an emphasis on their biological activities that have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Its pharmacological significance includes antidiabetic, antioxidant, anti-inflammatory, anticataract, antihypertensive, antiarthritic, antinociceptive, antibacterial, antifungal, hepatoprotective, analgesic, antihelminthic effects, etc. 16 , 17 Phytoconstituents such as iridoid diglucosides, secoiridoids, terpenoids, triterpenes, phenolic acid, flavones, and phytosterols were isolated from the plant. The antioxidant, anti-inflammatory, and free radical scavenging properties were reported for the isolated phytoconstituents.…”
Section: Introductionmentioning
confidence: 99%